Understanding the Challenges Faced by Neurodiverse Software Engineering Employees: Towards a More Inclusive and Productive Technical Workforce - Morris, Meredith Ringel; Begel, Andrew; Wiedermann, Ben (Proceedings of ASSETS 2015, 2015)
Technology workers are often stereotyped as being socially awkward or having difficulty communicating, often with humorous intent; however, for many technology workers with atypical cognitive profiles, such issues are no laughing matter. In this paper, we explore the hidden lives of neurodiverse technology workers, e.g., those with autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), and/or other learning disabilities, such as dyslexia. We present findings from interviews with 10 neurodiverse technology workers, identifying the challenges that impede these employees from fully realizing their potential in the workplace. Based on the interview findings, we developed a survey that was taken by 846 engineers at a large software company. In this paper, we reflect on the differences between the neurotypical (N = 781) and neurodiverse (N = 59) respondents. Technology companies struggle to attract, develop, and retain talented software developers; our findings offer insight into how employers can better support the needs of this important worker constituency.
Best Paper Award